If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x-6x+9=8-5x
We move all terms to the left:
x-6x+9-(8-5x)=0
We add all the numbers together, and all the variables
x-6x-(-5x+8)+9=0
We add all the numbers together, and all the variables
-5x-(-5x+8)+9=0
We get rid of parentheses
-5x+5x-8+9=0
We add all the numbers together, and all the variables
1!=0
There is no solution for this equation
| 37=-3+5(x=+6) | | X×y=0 | | 4x2-11x-33=0 | | 2w=1/9 | | (1/5)x+3=6 | | .333333333(6x+12)-2(x-7)=19 | | p-6=p-1+p-10 | | 25−6x=14+5x | | 4x+96=4x-24 | | 1.9s+6=3.1-6 | | 8=2r-5r | | ^x+2=11 | | 3x+-2(x+1)=-7 | | d/1.3=1.24 | | 3h-4=h+6 | | 13b-3b=20 | | 18p^2=12-15p | | 27=26p-1 | | -854t^2+64000t-150000=0 | | z÷11.4=6 | | 4=6r | | 5(x-3)+3=-12 | | 5x÷-x÷6=14 | | -854t^2+64000-150000=0 | | a+.93=1.42 | | 3(x+1)+2=x+9 | | 4-1/2a=6-a | | q^2+49q+144=0 | | -12=6(x+6)+6x | | q^2+49+144=0 | | 5(3x+6)=-14+29 | | 5x÷2-x÷6=14 |